Description of Parenting Styles of Parents with Autistic Children and Their Accompaniment Treatment - Belaweni, Boy Marjes; Junias, Marylin Susanti (Universitas Nusa Cendana, 2025)
Abstract. This study aims to describe the parenting styles of parents and the treatments provided to children with autism. The research employed a descriptive quantitative method with purposive sampling, involving 20 parents of children with autism aged 3–6 years at the Autism Service Center in Kupang. The instrument used was the PSDQ-Short Version questionnaire, which has been tested for validity (r > 0.422) and reliability (α = 0.912). The results showed that the democratic parenting style was the most widely applied, especially by parents aged 30–54 years with high school and undergraduate education. Meanwhile, a combination of democratic and permissive parenting was found among parents aged 55 years with a postgraduate education. Speech therapy and behavioral therapy were the most frequently used (90.23%), while sensory therapy was less applied (72.18%). Keywords: Autistic Children, Parenting Styles, Treatment